LMX Differentiation and Voice Behavior: A Resource-Conservation Framework. (August 2020) - Dong, Yanan; Jiang, Jing; Rong, Yan; Yang, Baiyin
The purpose of this article is to investigate how and when leader–member exchange (LMX) differentiation influences employees' voice behavior by examining trust as a psychological process and two types of leader power as opposite moderators. Based on a sample of 61 teams from an energy corporation in China, we tested a moderated mediation model using multilevel structural equation modeling. The results show that LMX differentiation is negatively related to employees' trust in leaders and, in turn, reduces employees' voice behavior. Moreover, leader reward power negatively moderates the influence of LMX differentiation on employees' trust in leaders such that the relationship is stronger when leader reward power is low but not significant when leader reward power is high. Leader coercive power positively moderates the relationship such that it is stronger when leader coercive power is high but not significant when leader coercive power is low. Furthermore, these two types of power moderate the indirect relationship between LMX differentiation and employees' voice via their trust in leaders. This study is the first to unpack the mechanism that links LMX differentiation and voice behavior and the conditions under which LMX differentiation can exert influence. This study delineates a resource-based process with conservation of resources theory through which employees appraise the social stressor (LMX differentiation), perceive the value of future resource investment (trust), strategically respond to resource signals (leader power), and finally make resource investment decisions (voice behavior).